A recent surge of fulminant and early onset subacute sclerosing panencephalitis (SSPE) in the United Kingdom: An emergence in a time of measles. (September 2021) - Lam, Tanya; Ranjan, Rajesh; Newark, Kerensa; Surana, Snehal; Bhangu, Neeraj; Lazenbury, Abigail; Childs, Anne-Marie; Abbey, Ianthe; Gibbon, Frances; Thomas, Gareth; Singh, Jaspal; Prabhakar, Prab; et al.
Abstract: Background: Subacute Sclerosing Panencephalitis (SSPE) is a fatal progressive neurological disorder following measles infection. Methods: Cases were collated from Paediatric Neurology centres in the UK over 24 months from 2017 to 2019 and represent all cases referred to the National Viral Reference Department (VRD). Diagnosis was established with detection of a raised measles index, demonstrating intrathecal measles antibody production. Findings: Six children presented with SSPE over two years, with median age five years (range 2–7 years) and median latency period three years (range 2–6 years). The majority were exposed to measles during infancy. Atypical features were common, including visual impairment, focal and generalised tonic-clonic seizures, headache, vomiting and movement disorders. EEG demonstrated typical features in five cases, though not always at presentation. Initial MRI was normal in four cases, with two showing focal and widespread white matter changes. Antiviral and immunomodulatory treatment led to minimal or no improvement. All progressed to cognitive regression, seizures and neurological decline within six months. Interpretation: These cases demonstrate the highest incidence of SSPE in the UK since 2000, all progressing to acute fulminant disease, following younger age of onset, short latency period and atypical presentations. Recent global surges in measles cases raise the importance of clinician awareness of SSPE as a potential diagnosis in children with neurological regression. Herd immunity remains the key protective mechanism for infants and groups that cannot be vaccinated. Health care providers, educators and governments must ensure resources continue to target effective education and access to immunisation programmes, the only means to combat this devastating and fatal condition. Highlights: SSPE is a lethal progressive neurological disorder that follows measles infection. We present the most significant UK cohort in the last 20 years. Cases were younger than previously described cohorts, with short latency periods. Acute fulminant course occurred in all, with atypical symptoms and investigations. The majority were vaccinated, but exposed to measles before the scheduled MMR dose.